Association of habitual alcohol consumption with carotid atherosclerotic lesions: results from the Corinthia study. (25th November 2020) - Theofilis, P; Oikonomou, E; Vogiatzi, G; Lazaros, G; Tsalamandris, S; Mystakidi, V.C; Goliopoulou, A; Chasikidis, C; Miliou, A; Fountoulakis, P; Papaioannou, N; Papakonstantinou, M; et al.
Abstract: Introduction: Alcohol is implicated in the pathophysiology of cardiovascular diseases. However, it is also believed to play a cardioprotective role if consumed in appropriate amounts. Purpose: To assess the association between alcohol consumption and carotid atherosclerosis. Methods: In the setting of the cross-sectional Corinthia study, volunteers filled in questionnaires regarding drinking habits and were characterized as social drinkers (SD) or habitual alcohol consumers (HAC). Furthermore, they underwent carotid ultrasonography examination to evaluate the carotid intima-media thickness (cIMT). Thickness of cIMT>1.5 mm or protrusion >50% compared to adjacent segments was considered as atherosclerotic plaque. Results: HAC consumers were usually male (HAC: 61.1%, SD: 24.9%, p<0.001), smokers (HAC: 33.3%, SD: 23.5%, p<0.001) and frequently had a history of hypertension (HAC: 72.8%, SD: 67.5%, p=0.02) when compared to SD (Table 1). However, no significant differences were noted regarding other risk factors of atherosclerosis (Table). Notably, HAC had a greater extent of carotid atherosclerosis as demonstrated by an increased cIMT (HAC: 1.03±0.45mm, SD: 0.96±0.39mm, p<0.001) and carotid plaque burden (HAC: 27.7%, SD: 21.3%, p=0.004). Importantly, when taking into account the number of alcoholic drinks (in wine glasses), alcohol consumption of more than 1 wine glass resulted in significantly higher values of cIMT (1 wine glass: 1.00±0.42mm, >1 wine glass: 1.06±0.45mm, p=0.04) (Figure 1A) and extensive amount of carotid plaques (1 wine glass: 22.7%, >1 wine glass: 30.4%, p=0.02) when compared to consumption of 1 wine glass (Figure 1B). Conclusion: Habitual alcohol consumption of more than one wine glass is associated with a higher carotid atherosclerotic burden. Funding Acknowledgement: Type of funding source: None